COMPARISON OF ULTRASONIC PULSE VELOCITY TEST RESULTS WITH AND WITHOUT USING TRANSDUCER STABILIZER - Fajar Surya Herlambang; Evin Yudhi Setyono (Politeknik Negeri Semarang, 2020)
Some research on the Ultrasonic Pulse Velocity (UPV) test has not covered much about the problems encountered during the data collection process. Based on experience using UPV test equipment, it is known that instability occurs in reading the test results. This is caused by the inability of the operator, in maintaining the stability of the transducer both in its position and pressure, especially in the measurement with the overhead position. Therefore, in this study a tool was made to make the transducer stable in the test position. Comparison of measurement results shows that, the uncertainty of wave velocity measurement decreases from the range of 4% -17% to 0.2% -0.4%. Meanwhile, the uncertainty of measurement of wave travel time decreased from the range of 0.8% -14% to 0.1% -0.4%. This can be interpreted that, the level of accuracy of measurements using a transducer stabilizer is 99.6% -99.9%. Thus, the use of transducer stabilizers is believed to be able to improve measurement accuracy.